Navigating the impact of climate change in India: a perspective on climate action (SDG13) and sustainable cities and communities (SDG11) - Hussain, Sharfaa; Hussain, Ejaz; Saxena, Pallavi; Sharma, Ashish; Thathola, Pooja; Sonwani, Saurabh (Frontiers in Sustainable Cities, 2024)
Climate change is a global concern of the current century. Its rapid escalation and ever-increasing intensity have been felt worldwide, leading to dramatic impacts globally. The aftermath of climate change in India has brought about a profound transformation in India's environmental, socioeconomic, and urban landscapes. In 2019, India ranked seventh, among the most affected countries by extreme weather events caused due to changing climate. This impact was evident in terms of both, the human toll with 2,267 lives lost, and the economic damage, which accounted for 66,182 million US$ Purchasing power parities (PPPs). Over the recent years, India has experienced a significant increase in the number and frequency of extreme weather events, causing vulnerable communities. The country experienced severe air pollution problems in several metropolitan cities and was highlighted in the list of the world's most polluted cities. Additionally, India has become the most populous nation globally, boasting a population of 1.4 billion people, equating to ~18% of the global population, and experiencing an increased rate of consumption of natural resources.Owing to the country's current scenario, various climate mitigation strategies, including naturebased solutions, must be implemented to reduce such impacts and support India's target of achieving the Sustainable Development Goals (SDGs). This review tries to have a holistic understanding of the effects of climate change on different sectors to identify India's challenges in achieving SDG 13 and SDG 11. Finally, it also highlighted the future recommendations for climate change-related research from an Indian perspective.